2018
DOI: 10.18632/oncotarget.23866
|View full text |Cite
|
Sign up to set email alerts
|

Identifying characteristic miRNAs-genes and risk pathways of multiple sclerosis based on bioinformatics analysis

Abstract: Multiple sclerosis is a chronic autoimmune disorder of the central nervous system. In MS, the genetic susceptibility is high and currently there is no effective treatment. MicroRNA, a small non-coding RNA, plays a vital role in immune responses. Aberrant or dysfunctional miRNAs may cause several diseases, including MS, thus miRNAs and miRNA related genes may be therapeutic weapons against MS. Here, we identified 21 miRNAs in peripheral blood mono-nuclear cells from over 600 persons, including healthy controls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 55 publications
1
15
2
Order By: Relevance
“…Site-specific meta-analysis of publicly available data identified a subset of genes that were common across the three major sites of HNSCC (tongue, laryngopharynx, oropharynx); the pathways that were primarily enriched included focal adhesion and proteoglycans in cancer, and cell cycle, mitotic pathway, which are well known in various cancers [29][30][31][32][33][34][35][36][37]. Differential expression profiling of the tongue cancer cohort triaged based on the stage, pathology identified multiple candidate markers; JAM2, SMURF1, LY6E, MFN1 and SUPT16H.…”
Section: Discussionmentioning
confidence: 99%
“…Site-specific meta-analysis of publicly available data identified a subset of genes that were common across the three major sites of HNSCC (tongue, laryngopharynx, oropharynx); the pathways that were primarily enriched included focal adhesion and proteoglycans in cancer, and cell cycle, mitotic pathway, which are well known in various cancers [29][30][31][32][33][34][35][36][37]. Differential expression profiling of the tongue cancer cohort triaged based on the stage, pathology identified multiple candidate markers; JAM2, SMURF1, LY6E, MFN1 and SUPT16H.…”
Section: Discussionmentioning
confidence: 99%
“…Among the other above-mentioned genes, BCL2 was reported as highly expressed in RRMS patients [ 51 ], while STAT3, MYC, JUN, NF-κB, and PTEN were identified as candidate genes for the MS susceptibility [ 52 ]. The study of Kristjansdottir et al showed that an increased amount of transcription factor SP1 binds the risk allele of the CGGGG indel polymorphism significantly associated with MS [ 53 ], whereas TCF3 was found to be implicated in the gene transcription regulation observed in the pathogenic mechanisms of the disease [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may somewhat explain overall reduced lymphocyte populations following simulated spaceflight exposures, along with reduced thymic and splenic weights, as well. Interestingly, miR-199a and miR-142–3p target Il7R ( Luo and Fu, 2018 ), reducing its expression levels; however, in our report, mechanisms of this requires further investigation. Conversely, elevated IL-7R has been linked to multiple inflammatory diseases ( Anderson et al., 2011 ; Belarif et al., 2018 ; Willis et al., 2012 ).…”
Section: Discussionmentioning
confidence: 55%